The media, Equal Education and school learners : an investigation of the possibility of 'political listening' in the South African education crisis - Mufamadi, Azwihangwisi Eugene (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2014)
This study sets out to investigate democratic participation in South Africa and the role that media play and can potentially play within this context. It considers a social movement, as one way in which citizens can organise themselves and make their voices heard to improve their chances of making a meaningful contribution to democracy. It employs Susan Bickford's theory of 'political listening', which offers a potential solution to the lack of political representativeness and inclusiveness, by focusing on the way citizens relate to each other through speaking, listening and dialogue. This study examines whether the interaction between learners and the social movement Equal Education could be considered 'political listening', and the current and possible role of the media within this context of participation. The study also attempts to develop and make a contribution to the language of description for the theory of political listening in order to map it onto the data. Using evidence or data gathered through observation of Equal Education's youth group meetings with learners and in-depth interviews with learners, youth group facilitators, Equal Education staff members and journalists, this study shows how the interaction amongst learners and between Equal Education and learners could be considered political listening and how the social movement works as a democratic project which offers learners an opportunity to exercise their citizenship. Furthermore, it also details the current role of the media and possible role of the media as perceived by Equal Education, learners and by journalists who report on Equal Education's activities. The study does not make conclusive claims about whether 'political listening' occurs between Equal Education and learners and the media because the study is exploratory in nature and involves a lot of trial and error when it comes to applying the theory of political listening to interview and textual data, which is a communication context that the theory is only beginning to chart.
Keywords: Equal Education (Nonprofit organisation); Journalism, Educational -- South Africa; Educational equalization -- South Africa; Journalism -- Political aspects -- South Africa; Education -- Citizen participation; Educational change -- South Africa; Qualitative research